Comprehensive investigation of the mechanisms for pyrolyzing macromolecular networks in Hecaogou subbituminous coal by comparing the ethanolysis and flash pyrolysis. (15th September 2022) - Kang, Yu-Hong; Chen, Tao; Gao, Juan; Li, Fan; Hu, Lin; Liu, Guang-Hui; Lu, Cui-Ying; Li, Yan-Jun; Wei, Xian-Yong; Ma, Ya-Jun; Zong, Zhi-Min; Bai, Hong-Cun
Highlights: MMNs of IEP is analyzed by multiple non-destructive technical strategies. The MMNs in IEP consists of aliphatic (59.6%) and aromatic carbons (39.3%). Pyrolysis mechanisms are analyzed by correlation IEP E and IEPFP at the molecular level. Pyrolysis of MMNs produce organic species by cleaving the >C– X bridge bonds. Abstract: The organic macromolecular networks (MMNs) from Hecaogou subbituminous coal (HSBC) were investigated by multiple technical strategies, including SEM, 1 H and 13 C NMR, FTIR, XPS, TG/DTG, and flash pyrolysis (FP) technology. The pyrolysis mechanisms of MMNs were effectively investigated to release organic volatile species between ethanolyzed ( E ) inextractable portion (IEP E ) and FP of IEP (IEPFP ) at molecular level. In detail, solid-state 13 C NMR analysis shows that carbon skeleton of IEP mainly consists of aliphatic (59.6%) and aromatic carbons (39.3%). XPS analysis shows that the >C–OH groups, pyrrolic, and sulfonic sulfurs in IEP surface are the most abundant O-, N-, and S-containing species. FTIR analysis proves that the weak- and medium >Cal - X ( X denotes Cal <, H, O-, N<, and S-) in IEP could be cleaved during ethanolysis. Based on the destructive analysis with TG/DTG, the structure of MMNs in IEP features dissociating small molecular groups with different types >Cal - X bridge bonds, which facilitates the release of organic volatile species and then prevents the thermal condensation during pyrolysis process. Additionally, the relative content (RC) in IEP E of various organic species are as follows: chain alkanes (CAs, 18.5%), alkenes (0.9%), arenes (11.9%), and oxygen-containing organic compounds (OCOCs, 58.4%), while the RC of CAs (46.8%), alkenes (17.5%), arenes (16.8%), and OCOCs (13.8%) in IEPFP . Comprehensive investigation and detailed analysis the distribution of organic species further prove that the active hydrogen (H‧) cleave the >Cal - X of MMNs at different positions during the pyrolysis process to obtain more CAs, alkenes, alkanols, and phenols at molecular level.